2015
DOI: 10.1158/1940-6207.capr-14-0296
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Persistence of Oral Human Papillomavirus Type 16: The HPV Infection in Men (HIM) Study

Abstract: Persistent infection with oral HPV16 is believed to drive the development of most oropharyngeal cancers. However, patterns of oral HPV16 persistence remain understudied, particularly among HIV-negative individuals. Oral HPV16 persistence was evaluated among 1626 participants of the HPV Infection in Men (HIM) Study. Twenty-three oral HPV16-positive men who provided an oral gargle sample on ≥2 study visits were included in the analysis. Archived oral samples from all follow-up visits were tested for HPV16 using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 33 publications
1
45
1
Order By: Relevance
“…We found that oncogenic HPV-16 was most prevalent among men 50–69 years of age. Data from HIM study indicate that the high prevalence of HPV-16 among older men might be attributed to longer persistence of infection (17). The study reported that the prevalent oral HPV-16 infection persisted longer than newly acquired infections and the persistence of incident HPV-16 infection increased significantly with age (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that oncogenic HPV-16 was most prevalent among men 50–69 years of age. Data from HIM study indicate that the high prevalence of HPV-16 among older men might be attributed to longer persistence of infection (17). The study reported that the prevalent oral HPV-16 infection persisted longer than newly acquired infections and the persistence of incident HPV-16 infection increased significantly with age (17).…”
Section: Discussionmentioning
confidence: 99%
“…Data from HIM study indicate that the high prevalence of HPV-16 among older men might be attributed to longer persistence of infection (17). The study reported that the prevalent oral HPV-16 infection persisted longer than newly acquired infections and the persistence of incident HPV-16 infection increased significantly with age (17). Given the incidence of OPSCC is highest among this age group of men (4), it is crucial to explore whether persistent HPV-16 infection plays a role in the observed excess prevalence of oral HPV-16 infection, particularly because persistent infection might be driving the OPSCC carcinogenesis among older men.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to date suggests that most people who do acquire oral HPV infection generally clear the infection within 6-12 months, 15,16 and 80% of individuals who acquire an oral HPV infection clear the infection by 1 year, regardless of HPV type-specific infection. 15 However, some infections persist, for reasons yet to be identified, which may lead to higher risk for oncologic disease.…”
Section: Epidemiology Of Oral Hpv Infectionmentioning
confidence: 99%
“…15 Male gender, older age and current smoking have been found to be significantly associated with higher risk of HPV persistence. 16 Other factors that may be associated with persistent infection include high oral HPV viral load 17 and concurrent persistent cervical infection, although longterm natural history data are not available. 18 …”
Section: Epidemiology Of Oral Hpv Infectionmentioning
confidence: 99%
“…The dramatic cancer disparity of blacks versus whites in HPV-positive oropharyngeal cancer (61) is well established; updated data suggest that these patterns may be changing over time (62). A recent report on the long-term persistence of oral HPV16 infection in men (63) adds important new data to the scarce information currently available regarding the natural history of oral HPV in light of the rising incidence of oropharyngeal cancer among men. Current work is moving genomics to this prevention and early detection setting to identify molecular risk groups in the setting of oral HPV16 infection.…”
Section: Immunopreventionmentioning
confidence: 99%